2002
DOI: 10.1086/342059
|View full text |Cite
|
Sign up to set email alerts
|

Tickborne Encephalitis in an Area of High Endemicity in Lithuania: Disease Severity and Long‐Term Prognosis

Abstract: Of 250 consecutively admitted patients with central nervous system (CNS) infections who were treated during a 1-year period, all 133 patients with tickborne encephalitis (TBE) were included in a prospective follow-up study. TBE presented as mild (meningeal) in 43.6% of patients and as moderate or severe (encephalitic) in 43.6% and 12.8% of patients, respectively. Paralytic disease was observed in 3.8% of the subjects, and cranial nerve injury was observed in 5.3%. One patient died of TBE. Permanent CNS dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
181
4
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(216 citation statements)
references
References 20 publications
23
181
4
8
Order By: Relevance
“…It has been found that as much as 46 % of patients may suffer from postencephalitic symptoms (Haglund et al, 1996;Günther et al, 1997;Kaiser, 1999;Mickiene et al, 2002;Kaiser, 2011). The TBE virus (TBEV) belonging to the genus Flavivirus is a positive-sense single stranded RNA virus transmitted by ticks of the species Ixodes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that as much as 46 % of patients may suffer from postencephalitic symptoms (Haglund et al, 1996;Günther et al, 1997;Kaiser, 1999;Mickiene et al, 2002;Kaiser, 2011). The TBE virus (TBEV) belonging to the genus Flavivirus is a positive-sense single stranded RNA virus transmitted by ticks of the species Ixodes.…”
Section: Introductionmentioning
confidence: 99%
“…EE me tu lik vo re ran da ma vi du ti në ple o ci to zë [22], ku ri në ra to kia ið reikð ta kaip ki tais vi ru si niø me nin go en ce fa li tø at ve jais [23]. Ra dzi ðaus kie nës ir kt.…”
Section: Diagnostikaunclassified
“…Re mian tis ki tø ty ri mø duo me nimis, Vo kie ti jo je 10-14 % as me nø po EE tu ri ne ága lu mà, o 1,5-3,6 % at ve jø li ga bu vo mir ti na [36]. Kor ti kos te roi dø efek ty vu mas në ra iki ga lo ið tir tas ir áro dy tas, në ra at lik ta at si tik ti niø im èiø kon tro liuo ja mø kli ni ki niø ty ri mø [22]. Ta èiau Bal ti jos ir Ry tø Eu ro pos ða ly se pa cien tams, ser gantiems EE, gy dy ti daþ nai ski ria mi kor ti kos te roi dai [22].…”
Section: Gydymasunclassified
See 1 more Smart Citation
“…Težave so poimenovali postencefalitisni sindrom. Različni avtorji so ugotavljali predvsem glavobol, motnje spomina in/ali koncentracije, razdražljivost, motnje ravnotežja, okvare sluha, tresenje in ohromelost posameznih mišičnih skupin (35,(42)(43).…”
Section: Potek In Posledice Kme Pri Obolelihunclassified